Pengaruh Potassium Media terhadap Pertumbuhan Mutlak, Osmolaritas Hemolymp dan Energi Basal dari Pascalarva Vaname (Litopenaeus vannamei, Boone) - Kaligis, Erly (e-Journal BUDIDAYA PERAIRAN, 2016)
Absolute Growth, hemolymp  osmolality, oxygen consumption, and basal energy of  Litopenaeus vannamei postlarvae were investigated. After post larval stage, PL-20, the postlarvae were acclimatized from sea water (25 ppt) to low salinity  water (2 ppt) over 96 h. Treatments consisted of different concentration of K+added to distilled water. Four different levels of K+ (0, 30, 60, and 90 ppm) were utilized. Ten shrimp were placed in triplicate 40-L glasses aquarium.  Results from the 42-day K+ growth trial indicated significant differences (P< 0.05) in absolute growth, hemolymp osmolality,  oxygen comsumption, and  basal energy. The values in treatment A was significantly higher than than those under the other four treatments. The results suggest treatment C were the optimum K+ level for culture  vaname postlarvae in low salinity water. Keywords :  Litopenaeus vannamei, oxygen comsumption, hemolymp